Oxyresveratrol inhibits cellular tyrosinase-related oxidative stress-induced melanogenesis in B16 melanoma cells - Teerapat Rodboon, Sarawoot Palipoch, Seiji Okada, Nisamanee Charoenchon, Yaowarin Nakornpakdee, Prasit Suwannalert (Journal of Applied Pharmaceutical Science, 2020)
Cellular oxidative stress is caused by an imbalance in the redox status and manifests as hyperpigmentation disorders. Reactive oxygen species, particularly hydrogen peroxide (H2O2) as the highly reactive hydroxyl radicals, promote the melanin production through the induction of tyrosinase enzyme activity. In this study, the antioxidant activity of oxyresveratrol was investigated by 2,2'-azino-bis-3-ethylbenzothiazoline-6-sulfonic acid (ABTS) and 2,2-dipheny l-1-picrylhydrazyl (DPPH) assays. In addition, melanin biosynthesis, tyrosinase activity, and cellular oxidants due to the bioactive component, oxyresveratrol, were determined in B16 cells by melanin content assay, cellular tyrosinase activity assay, and the dichloro-dihydro-fluorescein diacetate (DCFH-DA) assay, respectively. Hydrogen peroxide induced the melanogenesis through tyrosinase activity-related cellular oxidants, whereas oxyresveratrol showed a potent antioxidant activity by DPPH and ABTS assays. At the concentrations of 10 and 12.5 μg/ml, oxyresveratrol significantly inhibited melanogenesis in B16 melanoma cells and also suppressed tyrosinase activity and cellular oxidants. Effective doses of oxyresveratrol inhibit melanogenesis through bioactivity of cellular tyrosinase-related oxidative stress.
Keywords: Oxyresveratrol, melanin, oxidative stress, tyrosinase.